Turismo regional no litoral do nordeste brasileiro - Araújo, Luana Lima Bandeira (2018)
This study has the objective to analyze the regional tourism in the coastal areas of the Northeast of Brazil especially in the Meio-Norte, Sertão and Zona da Mata regions. The intention of this analysis is to understand the construction of a fragmented tourism in the Northeast of Brazil, using a logic whose historical density gives rise to a higher level of integration between the states of Zona da Mata when compared to the states of Sertão and Meio-Norte. Plots of the region have in the past instituted a trend of urbanization of the coastal zone that shows the existence of a flow of tourists from the region itself. The study is based on the premise of the existence of tourist attractions capable of agglomerating a large part of the visitor flows due to the interventions and improvements of government policies, aiding the construction / remodeling of roadways that articulate these localities and dynamize the region. The methodological procedures used were bibliographic research and a statistical database. The statistical database was achieved through secondary data provided by governmental or regulatory institutions, as well as primary data obtained through research in some states (Ceará, Rio Grande do Norte, Paraíba, Pernambuco and Alagoas). Studying this dynamics we can observe that there is the existence of historical and political factors in the Meio-Norte, Sertão and Zona da Mata areas, which defined a greater integration between the states or not, although tourism in the Brazilian Northeast developed from the same process of structuring the tourism activity of sun and beach, mainly due to the bias of structural programs, such as the Programa de Desenvolvimento do Turismo (Tourism Development Program) - PRODETUR. This space built in the past, also called Rugosidade, dynamizes the urban network, materializing regional and diffuse tourism in the Northeast region of Brazil. We can conclude that Public Policies such as PRODETUR I and II, PRODETUR Nacional (National PRODETUR) and the Programa de Aceleração do Crescimento (Growth Acceleration Program) - PAC gave impulse to the spatial transformations, stimulating not only the international tourist flow, but they began to contribute to the intensification of the tourist flow in regional scale, since the beneficiation of infrastructures, mainly in the implementation and restructuring of roadways in the Northeastern Coast of Brazil.